Asymmetric Coding of Categorical Spatial Relations in Both Language and Vision - Roth, Jessica; Franconeri, Steven (Frontiers in Psychology, 2012)
Describing certain types of spatial relationships between a pair of objects requires that the objects are assigned different ‘roles’ in the relation, e.g. ‘A is above B’ is different than ‘B is above A’. This asymmetric representation places one object in the ‘target’ or ‘figure’ role and the other in the ‘reference’ or ‘ground’ role. Here we provide evidence that this asymmetry may be present not just in spatial language, but also in perceptual representations. More specifically, we describe a model of visual spatial relationship judgment where the designation of the target object within such a spatial relationship is guided by the location of the ‘spotlight’ of attention. To demonstrate the existence of this perceptual asymmetry, we cued attention to one object within a pair by briefly previewing it, and showed that participants were faster to verify the depicted relation when that object was the linguistic target. Experiment 1 demonstrated this effect for left-right relations, and Experiment 2 for above-below relations. These results join several other types of demonstrations in suggesting that perceptual representations of some spatial relations may be asymmetrically coded, and further suggest that the location of selective attention may serve as the mechanism that guides this asymmetry.